Recolonization through Reconstruction: A Critical Discourse Analysis of Donald Trump’s Insinuation about Gaza - Dr. Nazia Anwar; Isha Razzaq Butt (Journal for Social Science Archives, 2025)
The rebuilding of Gaza has emerged as a unifying theme in international political rhetoric especially within the discourse of major global leaders. This research critically examines the discourse of U.S. President Donald Trump on the reconstruction of Gaza and demonstrates how it showcases neo-colonial discourses. Drawing on Critical Discourse Analysis (CDA), this study examines how Trump’s lexical choices—"take over," "ownership," "level the land," and "rebuilt"—position Gaza as a passive, reliant territory and the U.S. as a heroic, outcome-focused superpower. His words build Gaza up as needing to be governed by someone else, thus making American intervention justified and saving. The analysis shows that these rhetorical practices are not ideologically innocent but tend to reinforce U.S. exceptionalism and legitimate further foreign intervention in the Middle East. In placing reconstruction under the guise of recolonization, Trump’s rhetoric supports the reproduction of global power differentials. This research uncovers the way language serves to express dominance through discourses of peace, progress, and humanitarianism.